Comparison of ATCOR Atmospheric and ELM Linear Empirical Correction Models Applied to WorldView-2 Images - Roa Melgarejo, Osman; Ariza, Alexander; Ramírez, Héctor Mauricio; León Rincón, Hermann (TECCIENCIA, 2018)
The use of remote sensing images for the characterization of the coastal marine ecosystems requires the prior removal of the atmospheric effects, which can be done in a semi-automated manner, by the use of algorithms based on alternative assumptions contained in the processing tools for different software packages. The main objective of this study was to statistically compare the spectral behavior of the coverages contained in a high-resolution WorldView-2 image atmospherically corrected according to the ATCOR and empirical linear models (ELM), using field spectroradiometry conducted in the insular areas of the archipelago of San Andres and Providence. The ATCOR correction model was applied through the PCI 2015 Geomatics software; regarding the ELM model, the ENVI 5.2 software was used. For the spectral comparison four (4) types of coverage were selected (vegetation, reef formations, beach sand and submerged sandbank), with twenty (20) replicas each, for a total of eighty (80) sampling points distributed in a stratified way in the image. The statistical results showed a linear correlation greater than 0.9 between the reflectance values for each of the bands (Blue, Green, Red and NIR-1) and indicate that both models of the atmospheric correction have a high capacity to eliminate the atmospheric effects present in this type of images. However, there are minor significant differences between the middle quadratic errors in the reflectance values for each band of the corrected images.